Biomedical Waste Management in Private Hospitals of Bangalore - P Sudarkodi (East Asian Journal of Multidisciplinary Research, 2023)
Hospital waste is now predicted as a major public health hazard. According to World Health Organization, every year millions of people globally die due to infections such as HIV, Hepatitis B, and C and hepatocellular cancer transmitted through unsafe healthcare practices. There are also shocking disclosures about used medical devices and other items getting recycled by corrupted traders in countries. This happens when the hospitals do not take adequate steps to disinfect the medical waste as required under the law. The present study emphasis on evaluation of Biomedical waste management in Private Hospitals of Bangalore.